Aus den Beständen der Galerie : 1984. - Galerie Michael Haas, Berlin (Berlin : Galerie Michael Haas, 1984)
Albrecht, Margerita ; Archipenko, Alexander ; Beckmann, Max ; Bloch, Albert ; Bouten, Armand ; Bratby, John ; Buchet, Gustave ; Campendonk, Heinrich ; Chia, Sandro ; Combas, Robert ; Copley, William ; Feibusch, Hans ; Feininger, Lyonel ; Felixmüller, Conrad ; Fetting, Rainer ; Gläsker, Horst ; Graubner, Gotthard ; Hayden, Henri ; Herbin, Auguste ; Hitz, Dora ; Hofer, Karl ; von Hofmann, Ludwig ; Kanoldt, Alexander ; Kemple, Hans Joachim ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kolle, Helmut ; Leistikow, Walter ; Ray, Man ; Minarik, Ladislav ; Morgan, Tony ; Nay, Ernst Wilhelm ; Paladino, Mimmo ; etc.
Aus den Beständen der Galerie : 1984, Galerie Michael Haas, Berlin, 1984
boek